Impact of Different Depths of Transplanting by Machine Transplanter on Growth and Yield Performance of Rice Variety (Bw 361) - Sivaneson, S.; Vijayakumari, V. (University of Jaffna, 2019)
Depth of transplanting is an important factor which influences the grain yield in rice production systems by determining the number of tillers. Field trial was conducted to evaluate the growth and yield response of different planting depths of seedlings of mechanical transplanted rice. Four rows of behind-walk type paddy KUBOTA (SPW 48c) transplanter was used with 30 cm row spacing and five different planting depth (0.7, 1.4, 2.1, 2.8 and 3.7 cm), and replicated four times. The growth parameters of plant height, number of tillers, root length and yield parameters of panicle per hill, panicle length, and grain yield were recorded. Plant height (cm) during vegetative period, was significantly (p<0.05) higher at shallow planting depth of 0.7 cm. Root length and panicle length were not significantly influenced by depth of planting. The number of tillers per hill was significantly (p<0.05) differed among depth of planting. A positive correlation was observed between depth and tillers per hill up to 2.1 cm depth. The maximum number of tillers per hill and panicle numbers per hill were recorded at the depth of 2.1 cm. Results revealed that the planting depth of 2.1 cm produces significantly higher tillers, panicles per hill and grain yield. Therefore, 2.1 cm planting depth is more appropriate for cultivation of Bw361 variety in machine transplanting system in low country dry zone of Sri Lanka.
Keywords: Mechanical transplanting; Planting Depth; Rice; Yield